(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2025)
Dopamine receptors (nomenclature as agreed by the NC-IUPHAR Subcommittee on Dopamine Receptors [375]) are commonly divided into D1-like (D1 and D5) and D2-like (D2, D3 and D4) families, where the endogenous agonist is dopamine.